Teori Siklus Peradaban: Studi Komparatif Pemikiran Ibnu Khaldun (W. 1406) dan Malik Bennabi (W. 1973) - Yahya Muhaimin Nur; Hajar Ismail (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This article examines a comparative analysis of civilizational cycle theories proposed by two prominent Islamic thinkers, Ibn Khaldun and Malik Bennabi. Ibn Khaldun adopts a sociological approach by emphasizing the concept of ‘asabiyyah (social solidarity) as the primary force in the formation and decline of civilizations. In contrast, Malik Bennabi highlights a psycho-religious approach by focusing on the role of ideas, creativity, and human spirit in determining the destiny of a civilization. This article aims to analyze the similarities and differences between their perspectives and to assess the relevance of their ideas in understanding the dynamics of modern civilization. The study employs a qualitative approach based on library research and applies a comparative analytical method to provide a clear philosophical examination of the civilizational cycle theories of Ibn Khaldun and Malik Bennabi. The findings indicate that the approaches of Ibn Khaldun and Malik Bennabi are complementary rather than independent and should be understood as operating simultaneously. While Ibn Khaldun emphasizes external and structural aspects, Malik Bennabi focuses on internal and spiritual dimensions. The integration of these two perspectives provides a solid theoretical foundation and serves as a source of inspiration for the development of a sustainable Islamic civilization.